Induction of the swallowing reflex by electrical stimulation of the posterior oropharyngeal region in awake humans - Zakir, H.M. (2012)

(untitled)
We designed an electrical stimulation system to safely and reliably evoke the swallowing reflex in awake humans, and then examined the neural control of reflex swallowing initiated by oropharyngeal stimulation. A custom-made electrode connected to a flexible stainlesssteel coil spring tube was introduced into the pharyngeal region through the nasal cavity and placed against the posterior wall of the oropharynx. Surface electrodes placed over the suprahyoid muscles recorded the electromyogram during swallowing. Swallowing reflexes were induced several times by 30 s of repetitive electrical pulse stimulation (intensity: 0.2–1.2 mA, frequency: 10–70 Hz, pulse duration: 1.0 ms). The onset latency of the swallowing reflex was measured over the 10–70 Hz frequency range. In addition, the two time intervals between the first three swallows were measured. The onset latency of the swallowing reflex became shorter as the stimulus frequency increased up to B30 Hz. Once the frequency exceeded 30 Hz, there was no further reduction in the latency. This finding was consistent with those of previous studies in anesthetized animals. The time intervals between successive swallowing reflexes did not change with increased stimulus frequencies. Furthermore, prolonged stimulation often failed to elicit multiple swallowing reflexes. The frequency dependence of onset latency suggests that temporal summation of pharyngeal afferents is required to activate the medullary swallowing center. This reliable stimulation method may help in rehabilitation of dysphagic patients without causing aspiration.